Symmetric Cryptosystem Based on Chaos Structured Phase Masks and Equal Modulus Decomposition Using Fractional Fourier Transform - Girija, R.; Singh, Hukum (3D research, 2018)
Chaotic structured phase masks (CSPM), equal modulus decomposition (EMD) and fractional Fourier transform are potentially proposed to design the effective symmetric cryptosystem. The encryption and decryption process of our proposed system is completely established by using double random phase encoding (DRPE) in fractional Fourier domain. Frequently, random phase mask (RPM) are used routinely as secret key in most of the DRPE schemes. Nevertheless, RPM are not optimally robust against many attacks. Henceforth, this method utilises chaotic structured phase masks in the place of random phase masks (RPM). CSPM are assembled with the help of logistic map, Fresnel zone plates (FZP) and radial Hilbert mask (RHM) functions. To design an effectual trap door one-way function, equal modulus decomposition (EMD) is performed for encryption and decryption procedure of our cryptosystem. Various asymmetric cryptosystem was designed for EMD; but constructing EMD effectively in symmetric cryptosystem based on chaos structured phase masks and fractional Fourier transform is considered as a novel work and it is employed. As a result, the proposed symmetric cryptosystem attains high robust and withstand many attacks. Numerical simulations are exhibited in order to validate our system and support the fact that our EMD and CSPM based cryptosystem is extremely suitable for securing images.